ANALISIS KETERAMPILAN BERBICARA PADA MATA PEMBELAJARAN BAHASA INDONESIA KELAS 4B DI SDN CIPONDOH 06 KOTA TANGERANG - Indah Zianira Fitri; Yayah Huliatunisa; Sunaryo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Speaking skills are one of the essential foundations in language learning, yet many elementary students still struggle when asked to express their ideas orally. This study explores the speaking skills of 4th grade students at SDN Cipondoh 06 Kota Tangerang in Indonesian language learning through storytelling activities. Using a descriptive qualitative approach, data were collected through observation, interviews, oral tests, and documentation, then analyzed with the Miles & Huberman model. The findings reveal that students’ speaking abilities vary widely: most have met the Minimum Mastery Criteria (KKM), especially in pronunciation and expression, while others still face challenges in intonation, vocabulary, and self-confidence. External factors such as family support, teaching strategies, and the social environment were also found to shape students’ performance. The study highlights that storytelling is an effective medium to foster confidence, enrich vocabulary, and improve oral communication. These results are expected to provide insights for teachers in designing more engaging learning strategies and for students in developing communication skills that are crucial for their future.